Healthcare providers' perspectives and needs related to the management of Pediatric Feeding Disorder: A focus group study - Kelsey Thompson; Cuyler Romeo; Meg Simione; Hayley Estrem; Jaclyn L. Pederson; William G. Sharp (PLoS ONE, 2026)
Pediatric feeding disorder is a prevalent, impactful diagnosis for children and their families. This diagnosis is heterogenous in presentation and requires the care of a multidisciplinary team of providers. Existing research suggests providers are underprepared to assess and treat pediatric feeding disorder, therefore more information on training and clinical practice is needed. This study conducted focus groups to describe the training journey of providers across all four pediatric feeding disorder domains (medical, nutrition, feeding skill, psychosocial). Seven focus groups (total of 25 providers) were conducted and analyzed using thematic analysis. Four themes were identified: differences in academic preparation, workplace infrastructure and access, desire for comprehensiveness and feasibility, and value of the family perspective. Overall, results point to opportunities to improve provider training and therefore patient care including academic exposure to pediatric feeding disorder and multi-disciplinary collaboration practices, increased access to mentorship, training, and evidenced-based resources, and enrichment of the research to practice pipeline with a focus on family-centered care.